Novel Hydrazone Derivatives and Their Tetracoordinated Metal Complexes - SARI, NURSEN; NARTOP, DILEK; KARCI, FIKRET; DISLI, ALI (Asian Journal of Chemistry, 2010)
New aroylhydrazone derivatives and their Co(II), Ni(II) and Cu(II) complexes have been synthesized and characterized by means of elemental analyses, molar conductances and magnetic measurements as well as electronic spectra, IR spectra, 1H NMR spectra, 13C NMR spectra and LC mass spectra. Ni(II) complexes were found to have general compositions [ML], where L = 2,6-dipiperidino-4-(2-hydroxybenzylidene hydrazino)-1,3,5-s-triazine; 2,6-dipiperidino-4-(5-bromo-2- hydroxybenzylidene hydrazino)-1,3,5-s-triazine, while other complexes have composition [ML2] (M = Co2+ or Cu2+). The infrared spectra indicate the coordination of imino nitrogen and phenolic oxygen atoms. Tetracoordinated structures are proposed for the Co(II) Ni(II) and Cu(II) complexes on the basis of magnetic evidence and electronic spectra.